Reflective capacity in nurses in specialist education: Swedish translation and psychometric evaluation of the Reflective Capacity Scale of the Reflective Practice Questionnaire - Silje Gustafsson; Åsa Engström; Britt‐Marie Lindgren; Sebastian Gabrielsson (Wiley, 2021)
Abstract Aim This study aimed to test the validity and reliability of the Swedish version of the Reflective Capacity Scale of the Reflective Practice Questionnaire in a nursing context. Design Non‐experimental and cross‐sectional. Methods The instrument was translated from English to Swedish using a translation and back‐translation procedure. Data for the validity and reliability analysis were collected from Registered Nurses in specialist education (n = 156) at two Swedish universities. Results The Swedish version of the Reflective Capacity Scale of the Reflective Practice Questionnaire is a valid and reliable instrument that assesses the reflective capacity of healthcare practitioners. Our findings suggest a unidimensional structure of the instrument, excellent internal consistency and good reliability. Conclusion The Swedish version of the Reflective Capacity Scale of the Reflective Practice Questionnaire has a degree of reliability and validity that is satisfactory, indicating that the instrument can be used as an assessment of reflective capacity in nurses.